Technical note: Ride comfort optimisation of Ford cargo truck cabin. (2nd December 2009) - Tuncel, Ozan; Sendur, Polat; Ozkan, Murat; Guney, Ahmet
One of the main challenges of heavy duty truck comfort optimisation is to make sure that natural frequencies of axis, chassis, and cabin and seat subsystems are well separated. The design objective should also be to avoid frequencies of these subsystems in the range 4-8 Hz, to which the human body is sensitive. The objective of this paper is to improve the Ford cargo truck cabin. We have avoided to make any changes regarding the design of the above-mentioned parts and to improve the driving comfort without increasing production costs. Therefore, the focus of the work has been to improve the cabin suspension elements (suspension springs and shock absorbers) in order to achieve the design objectives.